Corporate Governance and Bank Performance: Global Financial Crisis 2008 - Zaitul, Zaitul; Melmusi, Zerni; Ilona, Desi (Journal of Reviews on Global Economics, 2019)
This research examine the role of Corporate Governance on bank performance; pre and during global financial crisis 2008. Using 2006 to 2009 data of 27 banks listed in Indonesia Stock Exchange is as research sample. Board, Family and Foreign Ownership as an internal Corporate Governance mechanism and Audit Quality is a proxy for external mechanism. Moderated Regression Analysis is applied. The result shows that there is no role of Corporate Governance in pre-global financial crisis. In addition, this study documented that the role of Corporate Governance practices is poor during global financial crisis 2008, especially 2009. Research limitations: Internal Corporate Governance mechanism does not use board or audit committee characteristics, such as board independent and audit committee financial expertise. Bank should strengthen Corporate Governance system while financial crisis come and uniqueness of Indonesia Corporate Governance system enrich Corporate Governance literature. This research is a significant addition to Corporate Governance literature because of using data from unique business environment and Corporate Governance system as well as in global financial crisis.